The Influence of Contextual Approaches on Students' Mathematical Creative Thinking Skills in Elementary School - Indriani, Rina; Rahmiati, Devi; Puspita, Ari Metalin Ika (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to examine the influence of the contextual approach on elementary school students’ mathematical creative thinking skills at SD Negeri 2 Surodakan, Trenggalek, East Java. This research used a quantitative approach with a quasi-experimental design involving an experimental class and a control class. The subjects were fourth-grade students, with class IV-D as the experimental class taught using the contextual approach and class IV-B as the control class taught using conventional learning. The research instrument was an essay test designed to measure mathematical creative thinking skills based on fluency, flexibility, and novelty. Data were collected through pretest and posttest, then analyzed using normality, homogeneity, and independent sample t-tests with SPSS 22.0. The results showed that the experimental class score increased from 78 to 83, while the control class increased from 76 to 78. The hypothesis test obtained significance values of 0.000 and 0.001 < 0.05, so H₀ was rejected and H₁ was accepted. Thus, the contextual approach significantly influences students’ mathematical creative thinking skills and can be used as an effective alternative in elementary mathematics learning.